Plasma Heme Scavengers Alpha-l-Microglobulin and Hemopexin as Biomarkers in High-Risk Pregnancies - Grigorios Kalapotharakos; Katja Murtoniemi; Bo Åkerström; Esa Hämäläinen; Eero Kajantie; Katri Räikkönen; Pia Villa; Hannele Laivuori; Stefan R. Hansson (FRONTIERS MEDIA SA, 2022)
Women with established preeclampsia (PE) have increased plasma concentration of free fetal hemoglobin. We measured two hemoglobin scavenger system proteins, hemopexin (Hpx) and alpha-1 -microglobulin (A1M) in maternal plasma using enzyme-linked immunosorbent assay during the late second trimester of pregnancy in women with high and low risk of developing PE. In total 142 women were included in nested case-control study: 42 women diagnosed with PE and 100 controls (49 randomly selected high-risk and 51 low-risk controls). The concentration of plasma A1M in high-risk controls was higher compared to low-risk controls. Women with severe PE had higher plasma A1M levels compared to women with non-severe PE. In conclusion, the concentration of plasma A1M is increased in the late second trimester in high-risk controls, suggesting activation of endogenous protective system against oxidative stress.